Capability Level New Media Literacy of Special Class I Checkpoint Immigration Office Batam - Latief Bugi Windarto; Ignatius Agung Satyawan; Albert Muhammad Isrun Naini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of new media has more or less changed people's behavior and lifestyle in communicating via digital. Seeing the pace and direction of these changes, the Government must immediately develop and implement a new communication strategy related to the implementation of e-government; that the current Government has implemented to provide good services to the community effectively and efficiently. Researchers want to know and measure New Media Literacy's twelve New Media Literacy Jenkins levels. The method used is a quantitative research method with a purposive sampling technique. The researcher recommends that government institutions as public servants can improve the New Media Literacy of each employee so that employees can communicate with the community effectively and efficiently.